Simultaneous bilateral spontaneous pneumothorax in a patient with recurrent, extraosseous multiple myeloma. Issue 928 (1st February 2003) - Peters, F; Cathomas, G; Rothen, M; Thurnheer, R; Rutishauser, J
Abstract : A patient with simultaneous bilateral spontaneous pneumothorax (SBSP) due to pulmonary and pleural manifestations of recurrent multiple myeloma is presented. The patient died in shock of unknown cause. The diagnosis was suspected from pleural fluid examination showing an exudate with numerous plasmocytes. Macroscopically and histologically, the visceral organs and the bone marrow were infiltrated with multiple monoclonal proliferations of plasma cells staining positively for IgG and lambda chains. SBSP is a rare condition and may be caused by trauma, parenchymal lung disease, infections, or neoplasms. This is the first report of SBSP caused by pleuropulmonary infiltration of multiple myeloma.